(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
Tripping is one of buckling modes in stiffened plates which could be occurred in the stiffeners with high flexural rigidity and low torsional rigidity. Rule-base expressions for calculation of sectorial moment of inertia of angle-bar stiffeners are scattered. An expression for calculation of sectorial moment of inertia of angle-bar stiffeners is derived based on energy method and beam theory. Sectorial moment of inertia of different angle-bar stiffeners are calculated and compared with the values calculated by different classification society rules. It is found that some of the rule-based equations for calculation of sectorial moment of inertia of angle-bar stiffeners are inaccurate. Euler tripping stress of different angle bars are calculated by energy method and compared with rule-based equation and finite element method. It is found that, rule-based expression for calculation of polar moment of inertia of angle-bar stiffeners neglects one term, which could lead up to 10% overestimation of Euler tripping stress. DOI: http://dx.doi.org/10.3329/jname.v9i2.10443 Journal of Naval Architecture and Marine Engineering 9(2012) 105-111